Analisis Manajemen Risiko Usaha Mikro Challaqan Craft Menggunakan Kerangka ISO 31000 pada Industri Kreatif Florist - Tariza Mega Pratiwi Garini; Aulia Silvana; Haura Nurul Ilmi; Naura Rahadhatul Aisy; Alfiana (Indo Publishing, 2025)
Micro enterprises in the creative industry sector play a vital role in supporting the local economy but often face various risks that threaten their suistainability. Challaqan Craft is a florist business in Bandung Regency producing creative flower, money, snack bouquets, and hampers. This study apllies the ISO 31000-based risk management approach to identify, analyze, evaluate, and treat business risks. The researce uses a descriptive qualitative method through interviews and documentation. The results reveal 17 risks across six categories: market, marketing, financial, operational, human resources, and legal. Three risks are high, most are medium, and one is low. The applied treatment strategies include improving product quality, enhancing operational efficiency, optimizing digital promotion, and strengthening business legality. Implementing ISO 31000 helps the owner minimize negative impacts and strengthen business resilience amid competition in the florist industry.